Evaluating the effectiveness of protection orders in preventing further victimisation of female survivors of domestic violence in the City of Tshwane, South Africa - Gutura, Priscilla (University of Pretoria, 2025)
Thesis (PhD (Social Work))--University of Pretoria, 2024.